Survey On Overlaps Between Articles In Web Of Science And Scopus In Cardiovascular Field (2001 To 2010) - Seyed Javad Ghazi Mirsaeid; Zahra Pouramini (Tehran University of Medical Sciences, 2014)
Background and Aim: The lack of paying attention to overlap between two databases cause purchase of duplicate resources waste of funds. This study examined overlap of articles in the field of cardiovascular which was indexed in Scopus and Web of science databases during years 2001 to 2010.  Materials and Methods: In this study, at first, sub-headings in cardiovascular field from medical thesaurus (Mesh 2012) was extracted, then each keyword in the title of the articles in both databases were searched and articles retrieved. Then bibliographic information of these articles entered into Endnote X3 software and afterwards was arranged based on alphabetically title. As a result common articles between the two databases and unique articles to each database was determined. Using SPSS version 0.1.0.8 the amount of relative and traditional overlaps was calculated between the two databases.  Results: Totally 45,680 articles were retrieved. There were 27,979 common titles, 14,875 articles belonged only to Scopus and 2826 articles belonged to Web of Science. Finally traditional overlap was 61/5%. Overlaps of Web of Science with Scopus 65/28% and Scopus with Web of Science were 65/28% and 90/82% repectively. Conclusion: The amount of relative overlap between the two databases as well as relative overlaps from Scopus with Web of Science is more than the relative overlaps from Web of science with Scopus. It means many articles that have been indexed in Scopus don't exist in the Web of science.